Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Step-by-step explanation:
(jk−1) ÷j
[(-4)(-0.8) -1] ÷ (-4)
=[ 3.2 -1] ÷ (-4)
=2.2 ÷ (-4)
= -0.55
The solution of the expression "[tex]\frac{jk-1}{j}[/tex]" is "-0.55".
The given values are:
- j = -4
- k = -0.8
→ [tex]\frac{jk-1}{j}[/tex]
By putting the value of "j" and "k" in the given expression, we get
→ [tex]\frac{(-4)(-0.8)-1}{-4}[/tex]
By solving the brackets, we get
→ [tex]\frac{3.2-1}{-4}[/tex]
→ [tex]\frac{2.2}{-4}[/tex]
→ [tex]-0.55[/tex]
Thus the above response is correct.
Learn more:
https://brainly.com/question/25032806
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.